Modelling of river flushing and water quality in a tributary constrained by barrages - Mah, Yau Seng; Frederik Josep, Putuhena; Nor Azalina, Rosli (Emerald Group Publishing Limited, 2012)
In developing countries, natural river regimes are increasingly undergone human modifications. All these constraints strongly affect the river systems. However, study on minor tributary of modified river is few. Thus the interest of this paper is to explore a tributary due to extensively regulated flow regime of mainstem river constrained by two barrages. The mainstem and tributary are deteriorating in its water quality due to the existing estuarial barrage impoundment. However by inserting another barrage in the middle stretch, modelling efforts have shown that the fluvial quality in the tributary improves compared to the former conditions. This has indicated that barrage operations are offering chances of improving a constrained tributary in terms of flow, flushing capability and water quality. Modelling of river flushing and water quality in a tributary constrained by barrages.